2002
DOI: 10.1074/jbc.m207659200
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophanyl Substitutions in Apomyoglobin Determine Protein Aggregation and Amyloid-like Fibril Formation at Physiological pH

Abstract: Myoglobin is an ␣-helical globular protein that contains two highly conserved tryptophan residues located at positions 7 and 14 in the N-terminal region of the protein. Replacement of both indole residues with phenylalanine residues, i.e. W7F/W14F, results in the expression of an unstable, not correctly folded protein that does not bind the prosthetic group. Here we report data (Congo red and thioflavine T binding assay, birefringence, and electron microscopy) showing that the double Trp/Phe replacements rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 51 publications
1
62
0
Order By: Relevance
“…5; Table 1). These shifts are similar to the characteristic maximum difference at ∼541 nm observed for amyloid (Klunk et al 1999), and the differential absorbance values are comparable to levels observed for other amyloid and amyloid-like fibrils (Gross et al 1999;Chiti et al 2001;Sirangelo et al 2002;KoscielskaKasprzak and Otlewski 2003).…”
Section: Thioflavin T and Congo Red Binding To Aggregatessupporting
confidence: 63%
See 1 more Smart Citation
“…5; Table 1). These shifts are similar to the characteristic maximum difference at ∼541 nm observed for amyloid (Klunk et al 1999), and the differential absorbance values are comparable to levels observed for other amyloid and amyloid-like fibrils (Gross et al 1999;Chiti et al 2001;Sirangelo et al 2002;KoscielskaKasprzak and Otlewski 2003).…”
Section: Thioflavin T and Congo Red Binding To Aggregatessupporting
confidence: 63%
“…Protein solutions diluted to 1 mg/mL were incubated in 50 M CR (Chiti et al 2001;Sirangelo et al 2002;Srisailam et al 2002), 20 mM HEPES (pH 7.8) for 20 min. Absorption spectra were acquired using a Cary 1Bio UV/visible spectrophotometer (Varian) at 25°C and a scan rate of 300 nm/min with a 0.3-cm path length cuvette.…”
Section: Congo Red Spectral Shiftmentioning
confidence: 99%
“…pH 4.0, the W7FW14F apomyoglobin mutant adopts a soluble molten globule-like conformation similar to that of the wild-type protein (24). In this state, the A, G, and H helices are folded as in the native conformation, whereas the rest of the molecule is essentially unfolded (39 -44).…”
Section: Resultsmentioning
confidence: 99%
“…Protein Purification-Wild-type and W7FW14F mutant myoglobin were expressed and purified essentially as described elsewhere (24). Proteins were expressed in Escherichia coli BL21 strain as N-terminal His-tagged forms and purified via affinity chromatography on Ni 2ϩ -nitrilotriacetic acid resin (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation